Pengaruh Macam dan Konsentrasi Ekstrak Tomat Terhadap Pertumbuhan Anggrek Cattleya Secara In Vitro - Umul Barroroh; Umul Aiman (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2005)
The research  was  aimed to observe  the influence  of kinds and dosage  of tomato extract  on growth of orchid Cattleya planlet in the Murashige and Skoog media. The experiment was arranged in a completely random design  (2 x 3) + 1 control with three replications. The  first  factor  was maturity  of tomato consisted  of 2 levels i.e riped and  green tomato. The second factor was dosage of tomato  extract consisted  of 100 gram/liter, 150 gram/liter, 200 gram/liter, and with no tomato extract  as control. Result of the research  indicated  that  application of 100 g/liter of ripening  tomato extract gave the better growth of Cattleya orchid than the other treatments.